Use of vegetable covers as a strategy to reduce soil erosión and increase the yield of corn (Zea mays L.) - Sanabria Quispe, Samuel (2023)
Soil degradation is a problem facing agriculture, with water being the most important erosive agent, affecting, among others, crop yields. The objective of this study was to know the effect of four plant covers on soil erosion and starchy corn yield, in three locations in the Ayacucho region (Peru) during the 2018 - 2019 agricultural season. Five treatments were assigned: control, clover cover, vetch cover, vetch-oat cover, and mulch, in corn plots under a randomized complete block design (RCBD), with four blocks. Combined analysis of variance was used to evaluate the results. It was observed that soil erosion and corn yield were significantly (P < 0.001) influenced by plant cover and locations. Vetch-oat and clover cover significantly reduced soil erosion (–53 and –36%, respectively) due to the higher leaf biomass produced by both (6131 and 6052 kg ha–1, respectively). Clover cover produced the highest corn yield (3749 kg ha–1; +78%); while vetch-oats produced the lowest (1955 kg ha–1), without significant differences with the control. The highest production of biomass, N and C of the foliar coverages was produced in the location with the least slope; while the highest performance occurred in steeper areas. Clover cover turned out to be a better option to reduce soil erosion and increase corn yield.